IMPLIKASI REKOMENDASI PENANGANAN PELANGGARAN ADMINISTRASI PEMILIHAN TERHADAP PERWUJUDAN PEMILIHAN DEMOKRATIS - Hasbi Dermawan; Abdullah Abdullah; Gunawan Arifin (Universitas Tadulako, 2025)
This study aims to determine the implications of recommendations for handling violations of election administration on the realization of democratic elections and the legal character of recommendations for the results of handling violations of election administration. This research is a type of normative research using a theoretical approach, a legislative approach and a conceptual approach. Based on the results and discussions, in this study, it can be concluded that: (1) The authority of Bawaslu in receiving reports, clarifying, and issuing recommendations is not only a form of carrying out constitutional and legal duties, but also a tangible manifestation of participatory supervision involving the community. 2) The legal character of recommendations on the results of handling administrative violations in the election is still in a position that is not fully firm, both normatively and implementively. Although legally the formal recommendation of Bawaslu has an imperative nature because it contains an obligation to be followed up by the KPU, in practice there is still an interpretation gap that allows the KPU to re-examine the substance of the recommendation. The Constitutional Court Decision Number 104/PUU-XXIII/2025 is an important foundation for the reform of election law, which emphasizes the need to change the phrase